Givinostat for Becker muscular dystrophy: A randomized, placebo-controlled, double-blind study - Comi, Giacomo P.; Niks, Erik H.; Vandenborne, Krista; Cinnante, Claudia M.; Kan, Hermien E.; Willcocks, Rebecca J.; Velardo, Daniele; Magri, Francesca; Ripolone, Michela; van Benthem, Jules J.; van de Velde, Nienke M.; Nava, Simone; et al. (Frontiers in Neurology, 2023)
Objective No treatments are approved for Becker muscular dystrophy (BMD). This study investigated the efficacy and safety of givinostat, a histone deacetylase pan-inhibitor, in adults with BMD. Methods Males aged 18–65 years with a diagnosis of BMD confirmed by genetic testing were randomized 2:1 to 12 months treatment with givinostat or placebo. The primary objective was to demonstrate statistical superiority of givinostat over placebo for mean change from baseline in total fibrosis after 12 months. Secondary efficacy endpoints included other histological parameters, magnetic resonance imaging and spectroscopy (MRI and MRS) measures, and functional evaluations. Results Of 51 patients enrolled, 44 completed treatment. At baseline, there was greater disease involvement in the placebo group than givinostat, based on total fibrosis (mean 30.8 vs. 22.8%) and functional endpoints. Mean total fibrosis did not change from baseline in either group, and the two groups did not differ at Month 12 (least squares mean [LSM] difference 1.04%; p = 0.8282). Secondary histology parameters, MRS, and functional evaluations were consistent with the primary. MRI fat fraction in whole thigh and quadriceps did not change from baseline in the givinostat group, but values increased with placebo, with LSM givinostat–placebo differences at Month 12 of −1.35% (p = 0.0149) and −1.96% (p = 0.0022), respectively. Adverse events, most mild or moderate, were reported by 88.2% and 52.9% patients receiving givinostat and placebo. Conclusion The study failed to achieve the primary endpoint. However, there was a potential signal from the MRI assessments suggesting givinostat could prevent (or slow down) BMD disease progression.